1992
DOI: 10.1002/jmv.1890380215
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hepatitis C viraemia in caucasian patients with hepatocellular carcinoma

Abstract: Potential risk factors for the development of hepatocellular carcinoma were analysed in 40 Caucasian patients with this malignancy. A higher proportion (14 of 40; 35%) had evidence of hepatitis C virus (HCV) infection than had evidence of either hepatitis B virus (HBV) carriage (17.5%) or alcohol abuse (30%). In all 14 patients whose sera were reactive by HCV ELISA (Ortho second generation test), the presence of antibodies to HCV were confirmed by recombinant immunoblot assay (Ortho RIBA-2). Furthermore, two i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…The use of PCR technique has revealed that 86% of seven investigated HCV-Ab-reactive asymptomatic individuals were positive and viremia was confirmed. This result corresponds with one other study from Garson et al 19 in which HCV-RNA was detected in a total of 12 patients and represented 86% of the anti-HCV-positive group.…”
Section: Discussionsupporting
confidence: 91%
“…The use of PCR technique has revealed that 86% of seven investigated HCV-Ab-reactive asymptomatic individuals were positive and viremia was confirmed. This result corresponds with one other study from Garson et al 19 in which HCV-RNA was detected in a total of 12 patients and represented 86% of the anti-HCV-positive group.…”
Section: Discussionsupporting
confidence: 91%
“…HCV-RNA was detected by PCR in all patients with homozy gous [3-thalassaemia and hepatitis C, except in 1 (95.6%), indicating a high prevalence of viraemia, probably due to impaired immunity of the thalassaemic patients or to repeated infections by different HCV genotypes. This is supported by the following Findings: the prevalence of viraemia in patients with 'sporadic hepatitis C' was found to be as low as 50% in our laboratory [24], whereas in two studies by Garson et al [14,25], using the same set of primers with ours but with haemodialysis and patients with hepatocellular carcinoma, it was 89 and 86%, respec tively. Furthermore, persistent viraemia in the patients is suggested by the Finding of anti-HCV antibodies in all patients for a mean period of 40 months before the detec tion of HCV-RNA, as well as the demonstration of HCV-RNA in 8 patients at least twice in the last 2-3 years.…”
Section: Household Contactssupporting
confidence: 54%
“…In some patients, disease severity may be related to the duration of disease, but this is frequently difficult to establish in patients who may have acquired the disease by inapparent transmission in childhood. Other factors, including viral load, mode of acquisition, reinfections, host immunity, genetic factors, age, coexistent viral and parasitic infection and alcohol may conceivably determine the outcome of infection (31)(32)(33)(34). Our study did not address these factors but points to a possible relationship between geographic origin and the histological range of the disease for a e v e n genotype.…”
Section: Discussionmentioning
confidence: 83%